2022
DOI: 10.3390/nu14163343
|View full text |Cite
|
Sign up to set email alerts
|

Good Adherence to the Mediterranean Diet Lowered Risk of Renal Glomerular Impairment in Children: A Longitudinal Study

Abstract: Healthy diet patterns have a positive effect on chronic non-communicable diseases in the pediatric population, but the evidence is limited on the association between kidney impairment and adherence to a Mediterranean diet. We aim to determine the associations between Mediterranean diet adherence and longitudinal tubular and glomerular impairment in children. Based on four waves of urine assays conducted from October 2018 to November 2019, we assayed urinary β2-microglobulin (β2-MG) and microalbumin (MA) excret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The FFQ in the LBC application is based on a Mediterranean diet, which has been shown to have a wide range of benefits for health [ 3 ], for instance, preventing chronic diseases [ 4 , 5 ]. The FFQ used in the LBC application consists of 24 questions and returns feedback on 11 aspects of nutrition, which users can set as goals to follow.…”
Section: Introductionmentioning
confidence: 99%
“…The FFQ in the LBC application is based on a Mediterranean diet, which has been shown to have a wide range of benefits for health [ 3 ], for instance, preventing chronic diseases [ 4 , 5 ]. The FFQ used in the LBC application consists of 24 questions and returns feedback on 11 aspects of nutrition, which users can set as goals to follow.…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean diet is one of the dietary patterns with the healthiest outcomes, which has a positive role in protecting people from chronic non-communicable diseases. A longitudinal study found that children who adhere well to the Mediterranean diet have a lower risk of transient glomerular impairment [ 12 ]. Another randomized pilot trial indicated that a nutritional intervention based on the Mediterranean diet helps to reduce high glycated hemoglobin (HbA1c) and insulin levels and, therefore, to reduce the prevalence of prediabetes [ 13 ].…”
mentioning
confidence: 99%